2015
DOI: 10.1111/1556-4029.12702
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Childhood Deaths in Turkey Due to Yellow Phosphorus in Firecrackers

Abstract: Yellow phosphorus (YP) is a powerful protoplasmic poison used in the manufacturing of matches, pest poisons, firecrackers, firework cracker, lights for watches, military ammunition, and agriculture fertilizer. YP is extremely flammable and toxic and easily absorbed from the gastrointestinal tract. In this study, we examined childhood deaths from 1997 to 2012 resulting from the ingestion of firecrackers. The patients ranged from 2 to 15 years of age and were admitted to the hospital with a variety of symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Macroscopic examination of the liver has revealed yellowish discoloration and petechial bleeding on the liver surface (6,7). The lungs were found to be heavy due to pulmonary edema but no macroscopic abnormalities were detected in the heart, kidney, and spleen (7). The most common autopsy feature noticed in our study was congestion followed by petechial hemorrhage of the studied viscera.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Macroscopic examination of the liver has revealed yellowish discoloration and petechial bleeding on the liver surface (6,7). The lungs were found to be heavy due to pulmonary edema but no macroscopic abnormalities were detected in the heart, kidney, and spleen (7). The most common autopsy feature noticed in our study was congestion followed by petechial hemorrhage of the studied viscera.…”
Section: Discussioncontrasting
confidence: 45%
“…However, macrovesicular steatosis was not an early feature since all cases except one were noticed after 3 days. The earliest change we noticed was hepatic necrosis and sinusoidal congestion in a patient who survived for 8 h. One study from Turkey observed sinusoidal congestion, diffuse microvesicular steatosis, and increased round cells in the portal region of patients who died immediately whereas patients who survived longer showed massive periportal necrosis, acute inflammatory cells, macrophages, bile duct proliferation, pseudo glandular proliferation, and widespread cholestasis (7). Apart from ductal proliferation, features of cholestasis and steatosis were observed in the person who survived for the longest duration in our study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Over the last 5 years, it has become a common indication for emergency liver transplantation (LT) in South India. Reports of YP poisoning through its use in fireworks have also been reported from several other countries [4][5][6] (Figure 1).…”
mentioning
confidence: 66%